2020
DOI: 10.1002/ange.202008847
|View full text |Cite
|
Sign up to set email alerts
|

Removing Formaldehyde‐Induced Peptidyl Crosslinks Enables Mass Spectrometry Imaging of Peptide Hormone Distributions from Formalin‐Fixed Paraffin‐Embedded Tissues

Abstract: Linking molecular and chemical changes to human disease states depends on the availability of appropriate clinical samples, mostly preserved as formalin‐fixed paraffin‐embedded (FFPE) specimens stored in tissue banks. Mass spectrometry imaging (MSI) enables the visualization of the spatiotemporal distribution of molecules in biological samples. However, MSI is not effective for imaging FFPE tissues because of the chemical modifications of analytes, including complex crosslinking between nucleophilic moieties. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…However, analysis of lipids has proven difficult in this type of tissue due to their depletion during initial processing with organic solvents, which is further compounded by the remaining lipids being implicated in cross-binding with other structures in the tissue [ 12 , 13 , 14 ]. For this reason, protocols that are able to remove, or reverse, the cross-links and liberate these trapped biomolecules are currently being developed [ 15 ]. Among these, it was recently shown that the inclusion of an antigen retrieval step in the MALDI-MSI sample preparation protocol increased the number of certain solvent-resistant lipids, particularly phosphatidylcholine (PC), sphingomyelin (SM), and phosphatidylserine (PS) species, that can be detected [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, analysis of lipids has proven difficult in this type of tissue due to their depletion during initial processing with organic solvents, which is further compounded by the remaining lipids being implicated in cross-binding with other structures in the tissue [ 12 , 13 , 14 ]. For this reason, protocols that are able to remove, or reverse, the cross-links and liberate these trapped biomolecules are currently being developed [ 15 ]. Among these, it was recently shown that the inclusion of an antigen retrieval step in the MALDI-MSI sample preparation protocol increased the number of certain solvent-resistant lipids, particularly phosphatidylcholine (PC), sphingomyelin (SM), and phosphatidylserine (PS) species, that can be detected [ 16 ].…”
Section: Introductionmentioning
confidence: 99%